Addressing perioperative anxiety in surgical patients - Jed Duff; Salihah Asiri (Journal of Perioperative Nursing)
Perioperative anxiety is a common yet often underestimated psychological response to surgery that can significantly impact patient outcomes and overall health care experiences. As perioperative nurses we witness first-hand how fear and apprehension can affect our patients before surgery whether it’s an elective or emergency procedure.